The vertebral column of the hourglass dolphin (Lagenorhynchus cruciger, Quoy and Gaimard, 1824), with notes on its functional properties in relation to its habitat - Marchesi, María Constanza; Pimper, Lida Elena; Mora, Matias Sebastian; Proser de Goodall, Rae Nataly (Aquatic Mammals)
Fast-swimming dolphins have a relatively stable morphological configuration, explained partially by their vertebral morphology. The hourglass dolphin (Lagenorhynchus cruciger), an oceanic species, is one of the least known species of small odontocetes. The aim of this paper is to describe the osteology of the vertebral column of this species, relating the main morphological characteristics to swimming performance in an oceanic habitat. We also present five new records, with meristics and measurements of the postcranial skeleton in conjunction with an exhaustive characterization of each functional region of the vertebral column through morphometric and graphical interpretations. In this species, the stability of the mid-torso is reinforced by the lumbarization and high number of vertebrae. While the morpho-logical process indicates a mechanical advantage for the swimming muscles, the mid-torso appears to act as an "oscillatory beam" to store potential energy, working as an elastic spring. Tail displacements are mainly produced by the flexion of the peduncle, which undulates from a stable mid-region. As suggested for other fast-swimming dolphins, morphological adaptations in the hourglass dolphin fit a typical pelagic mode of life, with a highly stable column that minimizes energy consumption, increasing efficiency for prolonged swimming. Fil: Marchesi, María Constanza. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina Fil: Pimper, Lida Elena. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ecología, Genética y Evolución; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Mora, Matias Sebastian. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de ...